Treatment with somatostatin analogues and PRRT in metastatic middle ear adenoma with neuroendocrine features. (12th May 2021) - Lima Ferreira, Joana; Marques, Bernardo; Menke-van der Houven van Oordt, C Willemien; de Herder, Wouter W; Brabander, Tessa; Hofland, Johannes
Abstract : Summary: Middle ear adenomas with neuroendocrine features (ANEF) are rare, with an estimated 150 reported cases. They usually pursue an indolent clinical course. Four reported cases of middle ear ANEF with distant metastases were treated with surgery, external beam radiation therapy (EBRT) and chemotherapy. To date, no successful systemic treatment for malignant behaviour of this rare tumour has been reported. Long-acting somatostatin analogues (SSAs) and peptide receptor radionuclide therapy (PRRT) have been used in well-differentiated metastatic neuroendocrine tumours (NETs), but their use has never been described in cases of metastatic middle ear ANEF. We report two patients with grade 1 middle ear ANEF treated with surgery and EBRT. They had stable disease for several years, until clinical symptoms appeared and extensive metastases were detected on 68 Ga-DOTA 0 -Tyr 3 -octreotate (DOTATATE) PET/CT. Treatment with long-acting SSA was started, with stable disease for 1 year. Afterwards, despite undergoing local treatments, both patients presented progressive disease. Due to high-uptake metastases at 68 Ga-DOTATATE PET/CT, both cases underwent four cycles of PRRT with 177 Lu-DOTATATE, which secured disease control and improvement of quality of life in both. Similar to other well-differentiated NETs, SSA and PRRT could constitute efficacious therapeutic options in metastatic middle ear ANEF. Its neuroendocrine differentiation, potential to metastasize and somatostatin receptor type 2 expression prompt consideration and management of this disease as a neuroendocrine neoplasm. Learning points: Our cases oppose the 2017 WHO classification of middle ear adenoma with neuroendocrine features as a benign disease. This entity warrants long-term follow-up, as local recurrence or persistence of disease is reported in up to 18% of surgically treated patients. PET/CT scan with 68 Ga-labelled somatostatin analogues (SSA) can be used for staging of metastatic middle ear adenoma with neuroendocrine features. Unlabelled SSA and peptide receptor radionuclide therapy (PRRT) with radiolabelled SSA can be the first systemic therapeutic options for patients with advanced middle ear adenoma with neuroendocrine features.